Shariah Contract Implementation in Bank Syariah Indonesia’s Mobile Banking: A Compliance Perspective - Listiawati (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2025)
This study examines the implementation of Shariah contracts (akad) in the use of mobile banking at Bank Syariah Indonesia (BSI). Formed through the merger of three major Islamic banks, BSI seeks to deliver digital financial services that comply with Shariah principles. This paper analyses the main contracts embedded in BSI’s mobile-banking products and services, including murabahah, ijarah, and mudharabah. The study adopts a qualitative descriptive approach, drawing on a literature-based analysis and a case-study orientation to identify and evaluate Shariah compliance in digital transactions. The findings indicate that BSI has generally integrated Shariah contracts effectively within its mobile-banking system under the supervision of the Shariah Supervisory Board (Dewan Pengawas Syariah, DPS). Technological innovations implemented by BSI also play an important role in supporting financial inclusion and facilitating customer access to services. In conclusion, the implementation of Shariah contracts in BSI mobile banking is effective in meeting the growing demand for Shariah-compliant digital financial services.